Role of community health officers: opportunities and challenges - Batra, Namita; Sharma, Kamlesh K. (International Journal Of Community Medicine And Public Health, 2025)
Mid-level health care providers in India were introduced as community health officers under Ayushman Bharat in 2018. There were introduced with objective of providing comprehensive primary health care (CPHC) services through health and wellness centers (HWCs). It is the new cadre that leads the primary care team in providing services under essential care packages at HWCs. They are expected to perform different roles and functions as formulated under the guidelines by Government of India. The job title of community health officer gives the mid-level health care providers, provides opportunity in terms of autonomy, training, management of health and wellness center, leading the team etc., but they face several challenges while performing their tasks under CPHC. The aim of this review paper is to highlight the roles and functions of community health officers and opportunities and challenges they face while delivering services to people.